IMPLEMENTATION OF LEARNING MEDIA DURING THE PANDEMIC - Deni Nasir Ahmad (STKIP PGRI Lubuklinggau, 2022)
Implementation Of E-Learning Learning During Covid-19 Pandemic In SMP NEGERI 31 BEKASI. The Covid-19 pandemic that hit Indonesia and impacted the world led the Ministry of Education and Culture and ministry of Religious Affairs of the Republic of Indonesia to implement a policy of learning and working from home. Responding to this policy, SMP NEGERI 31 BEKASI held an E-Learning socialization and in the event SMP NEGERI 31 BEKASI stated that it was ready for E-Learning learning during the Covid-19 pandemic. Therefore, the aim of this research is to describe the implementation of E-Learning learning during covid-19 pandemic in SMP NEGERI 31 BEKASI whether it has been implemented or not after the socialization was carried out. This research uses a qualitative approach, with a descriptive type of research. The technique of collecting data by doing observation, interview and documentation. The research informants consisted of 23: madrasah principals, 6 teachers and 16 students. The technique of determining informants using purposive sampling with data analysis techniques using interactive data analysis techniques. The results showed that the implementation of E-Learning learning during covid-19 pandemic in SMP NEGERI 31 BEKASIafter conducting thquestioning, has been able to implement E-learning well. This is proven by doing 3 stages: the preparation stage, the implementation stage and the evaluation stage. However, there are some obstacles such as the lack of human resources in E-learning learning and limited internet quota for students.